Influencer Marketing and Marketplace Platforms: Driving Online Fashion Purchase Intention through Consumer Motivation - Muhammad Aqshel Revinzky; Andreas Recki Prasetyo; Camelia Rizki Agrina; Rd. Rifqi Dwisanto; Joval Ifghaniyafi Farras (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
Fashion is a form of self-expression that reflects a person's identity, lifestyle, and social status. In addition to being a basic need, fashion is also a means of visual communication that allows individuals to express their personality, aesthetic preferences, and cultural affiliations. Along with the development of technology, especially through online platforms and social media, fashion is also increasingly accessible to various groups, including the younger generation (generation z), who are heavily influenced by influencers and digital trends. Therefore, fashion is now not only related to the style aspect, but also to the ever-evolving social, cultural, and economic dynamics. One way to understand the dynamics of the behavior of the younger generation in the fashion industry is to look at the role of digital marketing, especially through influencer marketing and marketplace platforms. This study aims to determine the direct and indirect effects of influencer marketing, marketplace platforms, consumer motivation on online fashion purchase interest. This study uses a quantitative approach of the Descriptive Explanatory type that describes the relationship between variables with a population of 114 Generation Z. The sampling technique used Proportional Random Sampling totaling 80 generation z students. The results of the study show that directly and indirectly influencer marketing, marketplace platforms, consumer motivation have a significant effect on online fashion purchase interest. Based on the research that has been conducted, it is expected to enrich the understanding of Generation Z digital consumer behavior and contribute to the development of more relevant and impactful marketing strategies for the online fashion industry and provide practical benefits for marketers and brands in developing the right marketing strategies.